Muscle fiber diameter assessment in cleft lip using image processing. (1st November 2017) - Khan, MFJ; Little, J; Abelli, L; Mossey, PA; Autelitano, L; Nag, TC; Rubini, M
Abstract : Objective: To pilot investigation of muscle fiber diameter (MFD) on medial and lateral sides of the cleft in 18 infants with cleft lip with or without cleft palate (CL/P) using image processing. Material and Methods: Formalin‐fixed paraffin‐embedded (FFPE) tissue samples from the medial and lateral sides of the cleft were analyzed for MFD using an image‐processing program (ImageJ). For within‐case comparison, a paired Student's t test was performed. For comparisons between classes, an unpaired t test was used. Results: Image processing enabled rapid measurement of MFD with majority of fibers showing diameter between 6 and 11 μm. There was no significant difference in mean MFD between the medial and lateral sides, or between CL and CLP. However, we found a significant difference on the medial side ( p = .032) between males and females. Conclusion: The image processing on FFPE tissues resulted in easy quantification of MFD with finding of a smaller MFD on the medial side in males suggesting possible differences in orbicularis oris (OO) muscle between the two sexes in CL that warrants replication using larger number of cases. Moreover, this finding can aid subclinical phenotyping and potentially in the restoration of the anatomy and function of the upper lip.